«Скитальцы в восточных краях»: А. С. Грибоедов и Н. Н. Толстой - Белоусова, Е. В.
В статье автор касается нравственных проблем участия человека в братоубийственных войнах и духовных последствий этого явления. Показана антивоенная позиция русских писателей и поэтов, отражавших на страницах своих произведений события Кавказской войны 1817-1859 гг. Автор рассматривает творчество двух писателей, произведения которых о Кавказе той эпохи почти неизвестны читателям, – А.С. Грибоедова и Н.Н. Толстого. In this article the author touches upon the moral aspect of human participation in fratricidal wars and spiritual consequences of this deed. The author concentrates on the anti-war position of the Russian writers and poets who described the events of the Caucasus war of 1817-1859 in their literary works. The author draws attention to the literary creation of two Russian writers -Alexander Gribojedov and Nikolay Tolstoy , whose works on the Caucasus of that period of time are practically unknown to the general reader
Keywords: Литературоведение